Analisis Efisiensi Penggunaan Direct Route dari Poin JOG ke Poin CA Dibanding dengan ATS Route W17 Dan W17S di Yogyakarta MCA - Safrudin Kurniawan; Rany Adiliawijaya Putri Ekapuja (Langit Biru: Jurnal Ilmiah Aviasi, 2021)
Flight routes to and from Jakarta - Yogyakarta use the same ATS route namely W-17 and W-17S. The air traffic controllers in Yogyakarta Adi Sutjipto airport give solution by providing an alternative route for the flight route of Yogyakarta - Jakarta via the direct route JOG - CA. This study have goal to provide a comparison of efficiency on the use of the direct route JOG - CA than when using the ATS route JOG - W - 17 - W17 S. This study is a comparative study, the type of research with two or more variables that aim to distinguish or compare the results between the two study groups. From the survey results revealed that there are 83 % flight to Jakarta using direct route JOG - CA, another result is the direct route through the JOG – CA compared to the ATS route W 17 - W17S could save the average travel time of 4.38 minutes or 19.5% and could save fuel at least 856,252 kg and a maximum of 1,546,978 kg in a year or by 5.33% to 16.35%.